Citra Kurikulum Baru: Kesiapan Guru dalam Menerapkan Kurikulum Merdeka - Prihatini, Arti; Sugiarti (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Teachers are required to have pedagogic competence by applying the current curriculum. However, teachers have not implemented the curriculum, but have been asked to apply it in the Professional Teacher In-Service Program (PPG Daljab). Based on this, this study aims to describe the experiences of PPG Daljab students in implementing the Independent Curriculum. This research method is narrative inquiry. The research subjects were five PPG Daljab students, University of Muhammadiyah Malang. The results showed that initially the teachers were not ready to apply the Independent Curriculum because the teachers did not have sufficient knowledge and experience. Nevertheless, the PPG learning process which suggests the implementation of the Independent Curriculum encourages teachers to continue to innovate in learning in terms of planning, implementation, evaluation, and follow-up. In general, the process also experiences substantial and technical obstacles, but these can be overcome by the teacher by continuing to seek knowledge and add concrete experience through practice. Thus, the teacher also has a much more mature readiness after the teacher has finished experiencing the practical phase of field experience. The teacher responded that the Independent Curriculum was much easier to implement if the teacher had sufficient understanding and experience.